Sistem Informasi, Produktivitas UMKM, Dan Kontribusi Pemerintah Pada Peningkatan Kesejahteraan Masyarakat Demi Mewujudkan Desa Balesari Sebagai Desa Wisata - Endang Kartini; Supanji Setyawan; Deni Ramdani (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2017)
Balesari village Windusari District of Magelang District designated as a village built Tidar University during the period of 3 years. So, the researchers wanted to identify the productivity of SMEs in the village Balesari and the government's contribution to improving the welfare of society, especially in order to realize Balesari village as a tourist village. The observations were made with the sorting of data samples that match the criteria, using purposive sampling research sample using at least 5-8 respondents in each village, bringing the total amount to more than 30 samples. This study examined the role of accounting information system through the development of SME productivity. The mechanism accounting information system development there are some procedures that need to be understood and followed by the village community in order to obtain authorization Balesari administratively, ie License, IUI, TDI, HO Permit and others. Exploration Balesari village aims to create value added activities so that it can bring in revenue and tourists.